Simultaneous quantitative screening of 53 phytochemicals from Rheum tataricum L. roots: a comparative study of supercritical CO2, subcritical ethanol, and ultrasound-assisted extraction for enhanced antioxidant, antibacterial activities, and molecular docking study - Amangeldinova, Madina; Ersatır, Mehmet; Necip, Adem; Yilmaz, Mustafa Abdullah; Cimentepe, Mehmet; Kudrina, Nataliya; Terletskaya, Nina V.; Ozturk Cimentepe, Ozge; Yildirim, Metin (Frontiers in Plant Science, 2024)
In this study, Rheum tataricum L. extracts were obtained using various green extraction techniques, including supercritical CO2, subcritical ethanol, and ultrasound-assisted extraction, each performed under optimized parameters. The phytochemical content of the extracts was analyzed using the LC-MS/MS technique, quantifying 53 phytochemicals. Additionally, the in vitro antioxidant properties and antibacterial activities of the extracts were evaluated against Staphylococcus aureus and Enterococcus faecalis as gram-positive bacteria, and Escherichia coli and Pseudomonas aeruginosa as gram-negative bacteria. According to the results, the extracts were rich in catechin, epicatechin, cyranoside, and chlorogenic acid. Extracts obtained via ultrasonic extraction demonstrated stronger antioxidant properties. The IC50 values for the DPPH radical scavenging activity of obtained extracts ranged between 0.0173 mg/mL and 0.0400 mg/mL. The highest total phenolic content was found in the UAE-M-4h extract (213.44 mg GAE/mL). The extracts prepared with UAE-MeOH-2h-4h, UAE-EtOH-2h-4h, Sbc-EtOH-E-140-60-80, Sc-90 atm, and Sc-400 atm showed antibacterial activity against both Grampositive and Gram-negative bacteria at varying rates (MIC range: 31.25 to 250 µg/mL). Based on the all results, the ultrasound assisted extraction proved superior to the other techniques. This study, utilizing three different extraction methods with varying variables such as temperature, pressure, and extraction time, has provided significant insights into which extraction method should be employed for isolating specific phytochemicals or for therapeutic purposes, based on the differing antibacterial results observed. The findings highlight the importance of selecting the appropriate extraction method depending on the target phytochemical or desired antibacterial effect in treatment applications.